2019
DOI: 10.3390/nano9070962
|View full text |Cite
|
Sign up to set email alerts
|

Charge Storage Properties of Nanostructured Poly (3,4–ethylenedioxythiophene) Electrodes Revealed by Advanced Electrogravimetry

Abstract: PEDOT nanowires (NWs) directly grown on the conducting electrode of quartz resonators enable an advanced electrogravimetric analysis of their charge storage behavior. Electrochemical quartz crystal microbalance (EQCM) and its coupling with electrochemical impedance spectroscopy (ac–electrogravimetry or AC–EG) were used complementarily and reveal that TBA+, BF4− and ACN participate in the charge compensation process with different kinetics and quantity. BF4− anions were dominant in terms of concentration over T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In this context, we have analyzed the mass variations of poly-33″-DDTT during electrochemical n-doping employing the electrochemical quartz crystal microbalance (EQCM) ( Naoi et al, 1991 ; Buttry and Ward, 1992 ; Dini et al, 2021 ), i.e., a non-invasive tool that detects in situ the mass changes accompanying a solid-state electrochemical process ( Schiavon et al, 1994 ; Ward and Meyers, 2000 ). EQCM also represents a sophisticated tool at the basis of those advanced approaches ( Gao et al, 2017 ; Lé et al, 2019 ) that intend to discern the directions of the fluxes through the electrode/electrolyte interface for the different species involved in an electrochemically driven redox process at an electronically conducting polymer ( Arbizzani et al, 1999 ). In some examples of particular complexity, some researchers have coupled EQCM with AC-electrogravimetry ( Lé et al, 2019 ) and with electroacoustic techniques ( Gao et al, 2017 ) to elucidate the role of anions, cations, and solvent in the charge compensation mechanisms of PEDOT nanowires and dodecylsulfate-doped polypyrrole taking into account the modification of the viscoelastic properties of the polymers undergoing continuous electrochemical cycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, we have analyzed the mass variations of poly-33″-DDTT during electrochemical n-doping employing the electrochemical quartz crystal microbalance (EQCM) ( Naoi et al, 1991 ; Buttry and Ward, 1992 ; Dini et al, 2021 ), i.e., a non-invasive tool that detects in situ the mass changes accompanying a solid-state electrochemical process ( Schiavon et al, 1994 ; Ward and Meyers, 2000 ). EQCM also represents a sophisticated tool at the basis of those advanced approaches ( Gao et al, 2017 ; Lé et al, 2019 ) that intend to discern the directions of the fluxes through the electrode/electrolyte interface for the different species involved in an electrochemically driven redox process at an electronically conducting polymer ( Arbizzani et al, 1999 ). In some examples of particular complexity, some researchers have coupled EQCM with AC-electrogravimetry ( Lé et al, 2019 ) and with electroacoustic techniques ( Gao et al, 2017 ) to elucidate the role of anions, cations, and solvent in the charge compensation mechanisms of PEDOT nanowires and dodecylsulfate-doped polypyrrole taking into account the modification of the viscoelastic properties of the polymers undergoing continuous electrochemical cycling.…”
Section: Introductionmentioning
confidence: 99%
“…EQCM also represents a sophisticated tool at the basis of those advanced approaches ( Gao et al, 2017 ; Lé et al, 2019 ) that intend to discern the directions of the fluxes through the electrode/electrolyte interface for the different species involved in an electrochemically driven redox process at an electronically conducting polymer ( Arbizzani et al, 1999 ). In some examples of particular complexity, some researchers have coupled EQCM with AC-electrogravimetry ( Lé et al, 2019 ) and with electroacoustic techniques ( Gao et al, 2017 ) to elucidate the role of anions, cations, and solvent in the charge compensation mechanisms of PEDOT nanowires and dodecylsulfate-doped polypyrrole taking into account the modification of the viscoelastic properties of the polymers undergoing continuous electrochemical cycling. Moreover, EQCM has demonstrated its usefulness in the evaluation of the dynamics of polymerization in the case of the potential pulse sequence-based electrochemical deposition of polypyrrole ( Plausinaitis et al, 2015 ) and the verification of spontaneous adsorption phenomena consisting in the formation of adlayers of pyrrole on metallic substrates prior to any sequence of electrical polarization ( Plausinaitis et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential of this technique has been scarcely investigated for vertical capacitive nanostructures. Within this context, we have recently reported pioneer studies dealing with the comprehension of energy storage mechanisms of capacitive vertically-aligned nanostructures such as VOGNs [45] and silicon nanowires (SiNWs) [46], or pseudocapacitive materials, as for example poly(3,4-ethylenedioxythiophene) (PEDOT) nanowires, [47] by using the EQCM and associated techniques. In the particular case of VOGNs, in the presence of a propylene carbonate (PC) solution containing tetrabutylammonium tetrafluoroborate (TBABF 4 ), classical EQCM and its complementary counterpart ac-electrogravimetry (coupling of QCM and EIS technique developed by Gabrielli et al [48]) confirmed that BF 4 − anions are the major energy storage vector with high kinetics of interfacial transfer values and low transfer resistance, while cations and free solvent molecules provide non-negligible supporting roles [45].…”
Section: Introductionmentioning
confidence: 99%